2020
DOI: 10.3390/ai1030023
|View full text |Cite
|
Sign up to set email alerts
|

A Single Gene Expression Set Derived from Artificial Intelligence Predicted the Prognosis of Several Lymphoma Subtypes; and High Immunohistochemical Expression of TNFAIP8 Associated with Poor Prognosis in Diffuse Large B-Cell Lymphoma

Abstract: Objective: We have recently identified using multilayer perceptron analysis (artificial intelligence) a set of 25 genes with prognostic relevance in diffuse large B-cell lymphoma (DLBCL), but the importance of this set in other hematological neoplasia remains unknown. Methods and Results: We tested this set of genes (i.e., ALDOB, ARHGAP19, ARMH3, ATF6B, CACNA1B, DIP2A, EMC9, ENO3, GGA3, KIF23, LPXN, MESD, METTL21A, POLR3H, RAB7A, RPS23, SERPINB8, SFTPC, SNN, SPACA9, SWSAP1, SZRD1, TNFAIP8, WDCP and ZSCAN12) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 26 publications
3
55
0
Order By: Relevance
“…The TNFAIP8 was identified within the top 20 most relevant genes of the LLMPP series. Then, we validated the importance of TNFAIP8 by immunohistochemistry and by digital quantification using a machine-learning Weka-based segmentation method in a series of DLBCL from Tokai University Hospital, and we confirmed that high TNFAIP8 was associated with a poor overall survival of the patients [28]. TNFAIP8 acts as a negative mediator of apoptosis and may play a role in tumor progression.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…The TNFAIP8 was identified within the top 20 most relevant genes of the LLMPP series. Then, we validated the importance of TNFAIP8 by immunohistochemistry and by digital quantification using a machine-learning Weka-based segmentation method in a series of DLBCL from Tokai University Hospital, and we confirmed that high TNFAIP8 was associated with a poor overall survival of the patients [28]. TNFAIP8 acts as a negative mediator of apoptosis and may play a role in tumor progression.…”
Section: Introductionmentioning
confidence: 58%
“…In this analysis, the dependent variable was treated as a scale (continuous) because the values represent ordered categories with a meaningful metric, so that distance comparisons between values are appropriate. Of note, this differs from our previous publications in which the dependent (target) variables were dichotomic (high vs. low, or dead vs. alive) [27,28]. Another difference from our previous publications [27,28] is that we are using the values of the collapsed probes.…”
Section: Software and Artificial Neural Network Analysismentioning
confidence: 65%
See 3 more Smart Citations